Reduction in the acquisition rate of carbapenem-resistant Acinetobacter baumannii (CRAB) after room privatization in an intensive care unit. (March 2022) - Jung, J.; Choe, P.G.; Choi, S.; Kim, E.; Lee, H.Y.; Kang, C.K.; Lee, J.; Park, W.B.; Lee, S.; Kim, N.J.; Choi, E.H.; Oh, M.
Summary: Background: Acinetobacter baumannii is one of the major pathogens responsible for healthcare-associated infections, especially in intensive care units (ICUs). Aim: To evaluate the effect of room privatization in an ICU on the acquisition of carbapenem-resistant A. baumannii (CRAB). Methods: Between March and August 2017, a medical ICU was renovated from a multi-bed bay room to single rooms. Acquisition of CRAB was compared between patients admitted to the ICU over 18 months pre-renovation (September 2015 to February 2017) and post-renovation (September 2017 to February 2019). A Cox proportional hazard model was used with adjustment for demographics and comorbidities. Findings: Of the 901 patients, who contributed 8276 patient-days, 95 (10.5%) acquired CRAB during their ICU stay. The CRAB acquisition rate was significantly higher during the pre-renovation period (1.87 per 100 patient-days) than during the post-renovation period (0.39 per 100 patient-days) ( P <0.001). In the multi-variable Cox regression model, CRAB acquisition was significantly associated with the presence of a feeding tube (adjusted hazard ratio (aHR), 6.08; 95% confidence interval (CI), 2.46–15.06; P <0.001), continuous renal replacement therapy (aHR, 1.66; 95% CI, 1.09–2.53; P =0.019) and admission after renovation of the ICU to single rooms (aHR, 0.23; 95% CI, 0.12–0.41; P <0.001). Conclusions: Renovation of ICUs to single rooms is an efficient strategy to prevent transmission of multi-drug-resistant organisms and hospital-acquired infections.